Prime Minister's Decree No. 3217 of the year 2022 Amending Certain Provisions of the Executive Regulations of the Law on Organizing the Participation of the Private Sector in Infrastructure, Services and Public Utilities Projects, As Promulgated by Law No. 67 of the Year 2010 = قرار رئيس مجلس الوزراء رقم 3217 لسنة 2022 بتعديل بعض أحكام الائحة التنفيذية لقانون تنظيم مشاركة القطاع الخاص فى مشروعات البنية الأساسية والخدمات والمرافق العامة الصادر بالقانون رقم 67 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic